Peran Orang Tua dalam Meningkatkan Praktik Pembelajaran Pada Mata Pelajaran Fiqih Kelas VI di Madrasah Ibtidaiyah Darud Da'wah Wal Irsyad Mareto Kecamatan Tanete Rilau Kabupaten Barru - Mardhatillah , Mardhatillah; B, Burhanuddin; Shaleh, Muhammad; Darmawati, Darmawati; Alam, Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to determine the role of parents in improving learning practices in the subject of Islamic jurisprudence at the Darud Da'wah Wal Irsyad Mareto Elementary School, Tanete Rilau District, Barru Regency. This type of research is field research with a qualitative research model. This study uses interview, observation, and documentation data collection techniques. Then, data analysis is carried out by reducing data, presenting data, and drawing conclusions. After obtaining the existing data, the results of this study the author can conclude that the role of parents is very important in improving the practice of Islamic jurisprudence learning at the DDI Mareto Elementary School, active involvement, role models, and emotional support from parents have been proven to strengthen the understanding and experience of Islamic teachings by students. The supporting factors are harmonious family relationships that are able to provide motivation and attention to children, as well as active involvement in activities at the madrasah, while the inhibiting factors are busy parents or limited time so that parents find it difficult to accompany their children in learning